Novel compounds that target lipoprotein lipase and mediate growth arrest in acute lymphoblastic leukemia. Issue 10 (1st June 2018) - Nair, Rajesh R.; Geldenhuys, Werner J.; Piktel, Debbie; Sadana, Prabodh; Gibson, Laura F.
Graphical abstract: Abstract: Over the past decade, the therapeutic strategies employed to treat B-precursor acute lymphoblastic leukemia (ALL) have been progressively successful in treating the disease. Unfortunately, the treatment associated dyslipidemia, either acute or chronic, is very prevalent and a cause for decreased quality of life in the surviving patients. To overcome this hurdle, we tested a series of cylopropanecarboxamides, a family demonstrated to target lipid metabolism, for their anti-leukemic activity in ALL. Several of the compounds tested showed anti-proliferative activity, with one, compound 22, inhibiting both Philadelphia chromosome negative REH and Philadelphia chromosome positive SupB15 ALL cell division. The novel advantage of these compounds is the potential synergy with standard chemotherapeutic agents, while concomitantly blunting the emergence of dyslipidemia. Thus, the cylopropanecarboxamides represent a novel class of compounds that can be potentially used in combination with the present standard-of-care to limit treatment associated dyslipidemia in ALL patients.